DYNAMICS AND STRUCTURAL TRANSITIONS IN PUBLIC EXPENDITURE ON EDUCATION IN HARYANA (2000–2025): A TIME SERIES AND ECONOMETRIC EVALUATION - Sonam (ShodhSamajik: Journal of Social Studies, 2026)
This paper examines the evolution of public expenditure on education in the state of Haryana, India, over the period 2000–2025, with particular attention to structural shifts associated with major national policy interventions such as the Sarva Shiksha Abhiyan (2001), the Right of Children to Free and Compulsory Education Act (2009), and the National Education Policy (2020). Continuously reported, education-specific official expenditure figures for Haryana that are comparable across years are available in the public domain principally from the early 2010s onward; the study therefore combines a descriptive account of the earlier period, drawn from secondary literature, audit reports and press coverage of budget documents, with a quantitative time-series analysis of budget estimates, revised estimates and actual expenditure for the sub-period 2010–11 to 2025–26, compiled from Comptroller and Auditor General (CAG) reports and PRS Legislative Research's annual budget analyses. Using descriptive statistics, compound annual growth rate (CAGR) calculations, ordinary least squares (OLS) trend regression and a split-sample mean-comparison test, the study finds that while nominal education expenditure in Haryana grew at a compound annual rate of approximately 5.2 percent between 2018–19 and 2025–26, education's share of total state expenditure trended downward over the same broader period — from roughly 15–18 percent in the early-to-mid 2010s to under 13 percent by 2025–26. This divergence between rising nominal outlays and a falling budgetary share is interpreted as a structural transition in fiscal priority rather than a stable allocation pattern. The paper situates these findings within the broader Wagner's-law literature on Indian state finances, benchmarks Haryana against the National Education Policy 2020 financing target, and discusses the data-availability constraints that limit long-run econometric research on sub-national education finance in India.